2014
DOI: 10.1136/neurintsurg-2014-011294
|View full text |Cite
|
Sign up to set email alerts
|

Racial and insurance based disparities in the treatment of carotid artery stenosis: a study of the Nationwide Inpatient Sample

Abstract: Minorities and self-pay/Medicaid patients were less likely to receive carotid revascularization when asymptomatic-rather they were more likely to have treatment only after symptoms had developed. These findings suggest possible disparities in the degree of morbidity related to carotid artery stenosis, the likelihood of early detection, and/or the likelihood of treatment conditional on indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…5, 24-27 To date, it has been reported using the Nationwide Inpatient Sample database that asymptomatic self-pay/Medicaid patients are less likely to receive carotid revascularization, often waiting until becoming symptomatic. 28 One additional confounder might be an increased aversion to surgery among black patients, manifesting in a delay to surgery attributable to operative hesitancy. 29-31 These patients were cared for by the same group of surgeons, and received preoperative medical optimization similarly, supported by similar rates of treatment with at least one anti-platelet agent (78% vs. 88% for white and black patients, respectively; P =.45), in accordance with recommended management guildelines 32, 33 , and a statin (48% vs. 41% for white and black patients, respectively; P =.56).…”
Section: Discussionmentioning
confidence: 99%
“…5, 24-27 To date, it has been reported using the Nationwide Inpatient Sample database that asymptomatic self-pay/Medicaid patients are less likely to receive carotid revascularization, often waiting until becoming symptomatic. 28 One additional confounder might be an increased aversion to surgery among black patients, manifesting in a delay to surgery attributable to operative hesitancy. 29-31 These patients were cared for by the same group of surgeons, and received preoperative medical optimization similarly, supported by similar rates of treatment with at least one anti-platelet agent (78% vs. 88% for white and black patients, respectively; P =.45), in accordance with recommended management guildelines 32, 33 , and a statin (48% vs. 41% for white and black patients, respectively; P =.56).…”
Section: Discussionmentioning
confidence: 99%
“…had symptoms attributable to their carotid disease) was identified using the following ICD-9-CM codes previously reported in literature: 362.3(0–7), 362.84, 433.11, 433.31, 434.01, 434.91, 435. (0–3,8,9), and 781.4 (2,4,5). The primary outcome of interest was hospital readmission within 30-days of discharge from a hospitalization during which a carotid revascularization procedure had been performed.…”
Section: Methodsmentioning
confidence: 99%
“…Socioeconomic and racial status and type of insurance has consistently been a predictor in the rendering of medical care [4][5][6]. The Provider Utilization and Payment Data Inpatient Public Use File database can be utilized to study disparities in care of patients with…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the 2013 Centers for Disease Control Health Disparities and Inequalities Report notes that minorities continue to be of lower socioeconomic status, resulting in greater barriers to health care access and increased burden of disease [7]. Specifically, Brijinki, et al [5] showed that minorities were less likely to receive carotid revascularization when asymptomatic and Kao et al [4] demonstrated lower DES usage in patients with government insurance and the uninsured population.…”
Section: Study Cohortmentioning
confidence: 99%